2019
DOI: 10.1111/are.14049
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Fourier transform—near infrared reflectance spectroscopy method for the rapid proximate analysis of the greenshell mussel ( Perna canaliculus ) and king (Chinook) salmon ( Oncorhynchus tshawytscha )

Abstract: Greenshell™ mussel (GSM, Perna canaliculus) and king (Chinook) salmon (Oncorhynchus tshawytscha) are New Zealand's two major aquaculture species generating $380 million NZD in exports during the 2017–18 financial year. This study addresses the development and validation of a method based on Fourier transform—near infrared reflectance spectroscopy (FT‐NIRs) to determine proximate composition for both species to aid breeding‐, production‐ and consumer decisions. Rapid measurements of GSM (n = 176) were taken by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Briefly, values were obtained for crude protein via total Kjeldahl nitrogen (AOAC 981.10), total fat via acid hydrolysis (AOAC 948.15), moisture via gravimetry at 105 °C (AOAC 950.46), and ash via incineration (AOAC 920.153); total carbohydrate content was estimated by difference (i.e., 100 − % protein − % fat − % moisture − % ash). These wet chemistry data were supplemented with WB proximate composition data estimated using near infrared (NIR) spectroscopy and species-specific NIR models we previously validated [ 48 ]. NIR models were also employed to obtain proximate composition and information on selected lipid-based characteristics (e.g., fatty acid classes) in fish fillets, extending the ‘general composition’ data layer (N = 28 variables).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, values were obtained for crude protein via total Kjeldahl nitrogen (AOAC 981.10), total fat via acid hydrolysis (AOAC 948.15), moisture via gravimetry at 105 °C (AOAC 950.46), and ash via incineration (AOAC 920.153); total carbohydrate content was estimated by difference (i.e., 100 − % protein − % fat − % moisture − % ash). These wet chemistry data were supplemented with WB proximate composition data estimated using near infrared (NIR) spectroscopy and species-specific NIR models we previously validated [ 48 ]. NIR models were also employed to obtain proximate composition and information on selected lipid-based characteristics (e.g., fatty acid classes) in fish fillets, extending the ‘general composition’ data layer (N = 28 variables).…”
Section: Methodsmentioning
confidence: 99%
“…Near infrared spectroscopy (NIR) has drawn considerable interest for many reasons, including its portability, speed, cost-effectiveness, suitability for in-line as well as on-line analysis, and the ability to concurrently measure different parameters for a large number of samples [151][152][153][154][155][156][157]. Several studies reported on the use of NIR for meat quality assessment and the analyses of meat properties in live animals or carcasses due to the capability of IR light to penetrate several layers of tissue [151][152][153][154][155][156][157][158][159]. Two published papers demonstrated that the short wavelength radiation in the NIR region of the electromagnetic spectrum can potentially be utilized to non-invasively assess meat quality [152,154].…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%
“…There are a few other recent reports demonstrating the use of a NIR based analysis method for rapid and cost effective identification of crucial nutrients with high precision rates [161]. For example, recently, Miller et al [159] reported a NIR based method for quick assessments of various components of king salmon and greenshell mussels. Most of the demonstrated methods take minutes to prepare and analyze the samples as compared to the days required for the conventional wet-lab chemical assays.…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%